2015
DOI: 10.1007/s10965-015-0789-0
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of core-shell PS/PMMA expandable particles via seeded suspension polymerization

Abstract: Expandable core-shell beads were synthesized by dosing methyl methacrylate (and styrene) in a constant rate and polymerizing in the presence of polystyrene seeds and pentane. The morphological studies of beads indicated that there were larger poly(methyl methacrylate)-rich domains near the shell. The sizes of these domains were decreased towards the core of the particles. For better surveying the likely structures of domains and the extent of expansion agent diffusion, the beads having the shells formed with c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 24 publications
2
6
0
Order By: Relevance
“…The high magnification SEM images provided information about the change of the microspheres' surfaces after the seeded polymerization process. This result is in accordance with the literature [1,15,18] . These surfaces are characteristic of non-porous shells.…”
Section: Resultssupporting
confidence: 94%
“…The high magnification SEM images provided information about the change of the microspheres' surfaces after the seeded polymerization process. This result is in accordance with the literature [1,15,18] . These surfaces are characteristic of non-porous shells.…”
Section: Resultssupporting
confidence: 94%
“…Moreover, the presence of PMMA at the surface seems to hinder particle expansion, and a non-uniform foamed particle was obtained. This result is in agreement with a more recent study published by Heydarpoor et al [10] . The authors investigated similar systems of PS/PMMA core-shell expandable particles, by using pentane as the expansion agent.…”
Section: Introductionsupporting
confidence: 94%
“…Previous studies showed that this kind of morphology was expected [8,10] . This occurred because the polymerization rate is much faster than the diffusion of PMMA/MMA in the swollen PS particles.…”
Section: Tem Analysismentioning
confidence: 67%
See 1 more Smart Citation
“…It was reported that the average molecular weight of PMMA in core-shell particles is almost 5 times higher than the PMMA obtained in unseeded batch suspension polymerization due to high polymer concentration and diffusional limitations (gel effect) that take place from the beginning of the second step of polymerization, decreasing the termination rate. 4 Therefore, the high-molecular-weight PMMA synthesized in the second step of polymerization needed more time to be completely extracted.…”
Section: Resultsmentioning
confidence: 99%